Phase‐resolving direct numerical simulations of particle transport in liquids—From microfluidics to sediment. Issue 2 (20th June 2022) - Fröhlich, Jochen; Hafemann, Thomas E.; Jain, Ramandeep
Abstract: The article describes direct numerical simulations using an Euler–Lagrange approach with an immersed‐boundary method to resolve the geometry and trajectory of particles moving in a flow. The presentation focuses on own work of the authors and discusses elements of physical and numerical modeling in some detail, together with three areas of application: microfluidic transport of spherical and nonspherical particles in curved ducts, flows with bubbles at different void fraction ranging from single bubbles to dense particle clusters, some also subjected to electro‐magnetic forces, and bedload sediment transport with spherical and nonspherical particles. These applications with their specific requirements for numerical modeling illustrate the versatility of the approach and provide condensed information about main findings.